109k views
0 votes
-4x + 6 = 3x - 36

How do I solve this

User Luckongas
by
5.7k points

2 Answers

7 votes
Subtract 6 from both sides so you have -4x=3x-42 then subtract 3x from both sides to get -7x=-42 lastly divide negative 7 from both sides to get x=6
User Saheb Roy
by
6.3k points
4 votes

Answer:

x = 6

Explanation:

Step 1: Write equation

-4x + 6 = 3x - 36

Step 2: Solve for x

  1. Add 4x to both sides: 6 = 7x - 36
  2. Add 36 to both sides: 42 = 7x
  3. Divide both sides by 7: x = 6

Step 3: Check

Plug in x to verify it's a solution.

-4(6) + 6 = 3(6) - 36

-24 + 6 = 18 - 36

-18 = -18

User SmokersCough
by
6.0k points